Green biosynthesis of silver nanoparticles using Dregea volubilis flowers: Characterization and evaluation of antioxidant, antidiabetic and antibacterial activity. Issue 8 (3rd August 2021) - Das, Bhaskar; De, Arnab; Podder, Soumik; Das, Shilpa; Ghosh, Chandan Kumar; Samanta, Amalesh
Abstract: The present work was conducted to biofabricate silver nanoparticles (AgNPs) in single step employing aqueous extract of Dregea volubilis flowers and to investigate its antioxidant, antidiabetic and antibacterial activities. The AgNPs were characterized by UV-Visible spectroscopy, X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), field emission scanning electron microscopy (FESEM), energy-dispersive X-ray (EDX) spectrometry, high resolution transmission electron microscopy (HRTEM) and zeta potential study. The biofabricated AgNPs showed potential antioxidant activity for scavenging DPPH radical (IC50, 40.45 ± 5.06 μg/mL), ABTS radical (IC50, 78.49 ± 1.41 μg/mL), total antioxidant capacity (148.83 ± 2.99 mg GAE/g) along with remarkable inhibitory effects on α-amylase (IC50, 10.62 ± 0.22 μg/mL) and α-glucosidase (IC50, 6.49 ± 0.03 μg/mL). The AgNPs showed notable antibacterial activity in terms of zone of inhibition (in mm) against Pseudomonas aeruginosa (10.67 ± 0.44), Escherichia coli (9.33 ± 0.44), Bacillus subtilis (14.67 ± 0.60) and Staphylococcus aureus (15.67 ± 0.60).